Psychological capital and student success: the mediating roles of emotions, happiness, and mental health - Jhon Veri; Herio Rizki Dewinta (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2026)
Research on Psychological Capital (PsyCap) and student success in higher education remains fragmented, particularly regarding whether PsyCap contributes directly to student success or operates through psychological well-being mechanisms. This study addresses that gap by testing a structural model in which PsyCap functions as a psychological resource, student success as an academic outcome, and positive emotions, happiness, and mental health as subsequent well-being outcomes. Using an explanatory quantitative design, data were collected from 250 active students enrolled in private universities in Indonesia and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings show that PsyCap significantly strengthens optimism and resilience, while its effects on hope and self-efficacy are not significant. PsyCap also does not directly predict student success. However, student success significantly predicts positive emotions, happiness, and mental health. These results suggest that the role of PsyCap in academic outcomes may be more limited and indirect than often assumed, whereas student success appears closely associated with students’ emotional and psychological well-being. This study contributes by clarifying the structural relationships among PsyCap, student success, and well-being variables in private higher education.